1980
DOI: 10.7589/0090-3558-16.4.601
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Wild Mammals in Transmission of Pseudorabies to Swine

Abstract: Of 73 wild and domestic mammals tested from an area endemic for pseudorabies in swine, 16 showed natural pseudorabies virus infection, 8 from farms with no pseudorabies history. In transmission experiments with swine and raccoons (Procyon lotor), pseudorabies was not transmitted between raccoons but was transmitted reciprocally between raccoons and swine by contact and when either consumed infected carrion of the other. The fluorescent antibody tissue section test proved valuable in diagnosis of pseudorabies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Previous experimental studies have indicated that raccoons can transmit PV to swine (Kirkpatrick et al, 1980). Although a potential role for raccoons in PV transmission has been postulated, previous studies have had difficulty in identifying free-ranging raccoons with positive serum neutralizing titers (Wright and Thawley, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experimental studies have indicated that raccoons can transmit PV to swine (Kirkpatrick et al, 1980). Although a potential role for raccoons in PV transmission has been postulated, previous studies have had difficulty in identifying free-ranging raccoons with positive serum neutralizing titers (Wright and Thawley, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the raccoon may act as a sentinel for PV in certain areas. Raccoons have been found to approach swine farms and feed on assorted feedstuffs, swine carcasses, and garbage, in this and other studies (Kirkpatrick et al, 1980;Thawley and Wright, 1982). The identification of seropositive raccoons could be used to help assess the PV status of a geographic region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections in domestic swine can result in fatal encephalitis in newborn pigs, mild or subclinical infections in older animals (Tozzini et al, 1982;Romero et al, 2001), and abortion in pregnant sows (Baskerville, 1981); survivors are latently infected. Feral swine are a recognized reservoir of ADV (Kirkpatrick et al, 1980;Nettles and Erickson, 1984;Van der Leek et al, 1993;Capua et al, 1997;Lipowski, 2003) and thus represent a possible source for infection of domestic swine (Corn et al, 1986;Pirtle et al, 1989;Corn et al, 2004). The importance of this reservoir will increased with the successful eradication of ADV from domestic swine.…”
mentioning
confidence: 99%
“…Los cerdos juegan un papel muy importante en la ecología de la enfermedad porque varios subtipos de VIP pueden infectar simultáneamente a los cerdos 15 . La enfermedad de Aujeszky es otra infección viral en la que los cerdos son los únicos hospederos naturales y los principales reservorios, sin embargo, también puede afectar a otros mamíferos, incluyendo rumiantes, carnívoros y roedores, entre ellos especies de fauna silvestre como mapaches, zorrillos, zorras, coyotes y grandes felinos 14,16,17 . Además de esta diversidad de virus patógenos, se realizó la detección de anticuerpos frente a enfermedades bacterianas como leptospirosis, salmonelosis y brucelosis, las cuales tienen la capacidad de afectar a una amplia variedad de especies, y tienen potencial zoonótico.…”
Section: Introductionunclassified